Life in the tundra - Winner, Cherie (Minneapolis, MN : Lerner, 2003)
Examines the physical features, processes, and many different species of plants and animals that make up the ecosystem of Alaska's North Slope.
Alaska's North Slope tundra -- Tussock tundra -- Sedge-moss tundra -- Along the rivers -- Maintaining the balance -- People on Alaska's North Slope tundra.
Includes bibliographical references (p. 67) and index.
6.1
5-8
Keywords: Tundras; Tundra ecology; Ecology; Alaska